Global discourse on ICT and the shaping of ICT policy in developing countries. (May 2019) - Hanafizadeh, Payam; Khosravi, Bayan; Badie, Kambiz
Abstract: This paper provides a critique of information and communication technology (ICT) policies in developing countries. Based on critical discourse analysis (CDA) of Iranian government discourse in the case of electronic fund transfer at the point of sale (EFT-POS) system, we illustrate the influence of global discourse on the policies and their contributions to the outcomes. We also analyze how policy shaped the ways in which different actors were included and allowed to participate in the implementation process. We show that enhancing the mainstream criteria like the rate of ICT adoption and diffusion, do not necessarily mean that policy will reap the expected benefits. From this standpoint, we propose that the focus of debate in policy making and defining policy objectives should move beyond setting objectives exclusively adopted from global discourse to also considering local issues and concerns. In such conditions, there will be less resistance to the government plans and fewer social challenges. Highlights: Achieving high rates of diffusion and adoption does not necessarily mean that ICT policies will reap the expected benefits. Ignoring local views in ICT policy making contributes to challenges and unexpected results. Developing countries should not make ICT policy by relying on global discourse exclusively.